Generation Z Agriculture: Agrarian Literacy as a Pillar of Economic and Ecological Sustainability - Irmayani Irmayani; Jannatul Adnin; Irninthya Nanda Pratami Irwan (Penerbit Goodwood, 2025)
Purpose: This study aimed to explore the understanding of agricultural literacy among Generation Z (Gen Z) in Kecamatan Bacukiki Barat, Parepare, and to compare their understanding based on direct experience and literature. Methodology/approach: This research utilizes a descriptive qualitative approach, employing data triangulation for validity testing. In-depth interviews and participatory observations were conducted to collect data from the research participants. Results: The results show that Gen Z's agricultural literacy is moderate. Although they have a basic understanding of agricultural concepts, there is a lack of practical application. Understanding gained from direct experiences, such as involvement in agricultural activities or field visits, had a greater impact on encouraging real actions than knowledge gained solely from literature or written sources. Conclusions: Strengthening practical experiences in agricultural education is essential to enhance Gen Z’s understanding and participation in the agricultural sector. This can be achieved through internship programs, field practice, and collaboration with local farmers and educational institutions. Limitations: The research is limited to participants in Kecamatan Bacukiki Barat, Parepare, which may limit the generalization of the findings to other regions or populations. Contributions: This study contributes to understanding the agricultural literacy of Gen Z and emphasizes the importance of practical learning experiences for improving engagement and sustainability in the agricultural sector.